'Our time to recover': young men, political mobilization, and personalized political ties during the 2017 primary elections in Nairobi. Issue 4 (1st October 2020) - Rasmussen, Jacob; van Stapele, Naomi
ABSTRACT: In this article, we show how youth groups in Nairobi's poor settlements engage with politics while carving out a political space for themselves and providing a livelihood. In doing so, we challenge dominant neo-patrimonial narratives of youth radicalization and instrumentalized youth mobilization in relation to electoral processes. Based on long-term ethnographic engagements, we argue for more complex dynamics between local youth groups and politicians; dynamics informed by differently situated understandings and diverse experiences of democracy. We follow the emic use of the term kupona (Kiswahili word meaning recovery or healing) to approach youth's political engagements along lines of participation, recognition, and re-distribution, which all in different ways express demands for social recovery. Empirically, the article draws on events and examples from the primary elections in 2017, which provide a privileged frame for investigating local politics and responses to the recently initiated devolved government structure.